Brain computer interface via EEG signals - Koh, Ji Peng (2018)
Emotions are states in feeling that results in physical and psychological changes that influences thought, behaviour and action. A person’s true affective state can be hidden with words and action. Analysing a person’s brainwaves can reveal their affective state. This project makes use of two different stimuli types, still images with audio (IA clips) and movie clips. The objective of this project is to find out the accuracy of classifying emotions into six different classes. This project will also determine the effect of different stimuli types as well as the different orders of stimuli type on the effectiveness of elicitation of emotion. There will be two different orders of stimuli type. The first is movie clips followed by IA clips, called the MIA session. The second is IA clips followed by movie clips, called the IAM session.